Solve for x
x=\frac{\sqrt{256009}-3}{1280}\approx 0.392947906
x=\frac{-\sqrt{256009}-3}{1280}\approx -0.397635406
Graph
Share
Copied to clipboard
20x^{2}\times 32+3x=100
Multiply x and x to get x^{2}.
640x^{2}+3x=100
Multiply 20 and 32 to get 640.
640x^{2}+3x-100=0
Subtract 100 from both sides.
x=\frac{-3±\sqrt{3^{2}-4\times 640\left(-100\right)}}{2\times 640}
This equation is in standard form: ax^{2}+bx+c=0. Substitute 640 for a, 3 for b, and -100 for c in the quadratic formula, \frac{-b±\sqrt{b^{2}-4ac}}{2a}.
x=\frac{-3±\sqrt{9-4\times 640\left(-100\right)}}{2\times 640}
Square 3.
x=\frac{-3±\sqrt{9-2560\left(-100\right)}}{2\times 640}
Multiply -4 times 640.
x=\frac{-3±\sqrt{9+256000}}{2\times 640}
Multiply -2560 times -100.
x=\frac{-3±\sqrt{256009}}{2\times 640}
Add 9 to 256000.
x=\frac{-3±\sqrt{256009}}{1280}
Multiply 2 times 640.
x=\frac{\sqrt{256009}-3}{1280}
Now solve the equation x=\frac{-3±\sqrt{256009}}{1280} when ± is plus. Add -3 to \sqrt{256009}.
x=\frac{-\sqrt{256009}-3}{1280}
Now solve the equation x=\frac{-3±\sqrt{256009}}{1280} when ± is minus. Subtract \sqrt{256009} from -3.
x=\frac{\sqrt{256009}-3}{1280} x=\frac{-\sqrt{256009}-3}{1280}
The equation is now solved.
20x^{2}\times 32+3x=100
Multiply x and x to get x^{2}.
640x^{2}+3x=100
Multiply 20 and 32 to get 640.
\frac{640x^{2}+3x}{640}=\frac{100}{640}
Divide both sides by 640.
x^{2}+\frac{3}{640}x=\frac{100}{640}
Dividing by 640 undoes the multiplication by 640.
x^{2}+\frac{3}{640}x=\frac{5}{32}
Reduce the fraction \frac{100}{640} to lowest terms by extracting and canceling out 20.
x^{2}+\frac{3}{640}x+\left(\frac{3}{1280}\right)^{2}=\frac{5}{32}+\left(\frac{3}{1280}\right)^{2}
Divide \frac{3}{640}, the coefficient of the x term, by 2 to get \frac{3}{1280}. Then add the square of \frac{3}{1280} to both sides of the equation. This step makes the left hand side of the equation a perfect square.
x^{2}+\frac{3}{640}x+\frac{9}{1638400}=\frac{5}{32}+\frac{9}{1638400}
Square \frac{3}{1280} by squaring both the numerator and the denominator of the fraction.
x^{2}+\frac{3}{640}x+\frac{9}{1638400}=\frac{256009}{1638400}
Add \frac{5}{32} to \frac{9}{1638400} by finding a common denominator and adding the numerators. Then reduce the fraction to lowest terms if possible.
\left(x+\frac{3}{1280}\right)^{2}=\frac{256009}{1638400}
Factor x^{2}+\frac{3}{640}x+\frac{9}{1638400}. In general, when x^{2}+bx+c is a perfect square, it can always be factored as \left(x+\frac{b}{2}\right)^{2}.
\sqrt{\left(x+\frac{3}{1280}\right)^{2}}=\sqrt{\frac{256009}{1638400}}
Take the square root of both sides of the equation.
x+\frac{3}{1280}=\frac{\sqrt{256009}}{1280} x+\frac{3}{1280}=-\frac{\sqrt{256009}}{1280}
Simplify.
x=\frac{\sqrt{256009}-3}{1280} x=\frac{-\sqrt{256009}-3}{1280}
Subtract \frac{3}{1280} from both sides of the equation.
Examples
Quadratic equation
{ x } ^ { 2 } - 4 x - 5 = 0
Trigonometry
4 \sin \theta \cos \theta = 2 \sin \theta
Linear equation
y = 3x + 4
Arithmetic
699 * 533
Matrix
\left[ \begin{array} { l l } { 2 } & { 3 } \\ { 5 } & { 4 } \end{array} \right] \left[ \begin{array} { l l l } { 2 } & { 0 } & { 3 } \\ { -1 } & { 1 } & { 5 } \end{array} \right]
Simultaneous equation
\left. \begin{cases} { 8x+2y = 46 } \\ { 7x+3y = 47 } \end{cases} \right.
Differentiation
\frac { d } { d x } \frac { ( 3 x ^ { 2 } - 2 ) } { ( x - 5 ) }
Integration
\int _ { 0 } ^ { 1 } x e ^ { - x ^ { 2 } } d x
Limits
\lim _{x \rightarrow-3} \frac{x^{2}-9}{x^{2}+2 x-3}